Surrogate-based design optimisation tool for dual-phase fluid driving jet pump apparatus - Mifsud, Darren; Verdin, Patrick G. (Springer, 2019)
A comparative study of four well established surrogate models used to predict the non-linear entrainment performance of a dual-phase fluid driving jet pump (JP) apparatus is performed. A JP design flow configuration comprising a dual-phase (air and water) flow driving a secondary gas-air flow, for which no one has ever provided a unique set of design solutions, is described. For the construction of the global approximations (GA), the response surface methodology (RSM), Kriging and the radial basis function artificial neural network (RBFANN), were primarily used. The stacked/ensemble models methodology was integrated in this study, to improve the predictive model results, thus providing accurate GA that facilitate the multi-variable non-linear response design optimisation. An error analysis of all four models along with a multiple model accuracy analysis of each case study were performed. The RSM, Kriging, RBFANN and stacked models formed part of the surrogate-based optimisation, having the entrainment ratio as the main objective function. Optimisation problems were solved by the interior-point algorithm and the genetic algorithm and incurred a hybrid formulation of both algorithms. A total of 60 optimisation problems were formulated and solved with all three approximation models. Results showed that the hybrid formulation having the level-2 ensemble Kriging model performed best, predicting the experimental performance results for all JP models within an error margin of less than 10 % in 90 % of the cases.
Keywords: Dual-phase jet pump; Surrogate modelling; Global approximations; Global optimisation; Ensemble modelling; Genetic algorithm; Gaussian process; Radial basis function